Method for controlling physical properties of electrolytic copper foil and its manufacturing method
Patent Information
- Application Number
- JP2023544706
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-05-11
- Filing Date
- 2023-03-30
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2043-03-30
AI Technical Summary
【0025】 本発明によれば、電解銅箔の光沢度だけを調節して電解銅箔の引張強度、延伸率及び粗さ等の物性を容易に調節することができる。
Smart Images

Figure 0007633416000003 
Figure 0007633416000004 
Figure 0007633416000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for controlling the physical properties of an electrolytic copper foil, which can easily control the other major physical properties, such as tensile strength, elongation rate and roughness, by adjusting only the gloss of the electrolytic copper foil, and a method for manufacturing the same. [Background technology]
[0002] Recently, the demand for secondary batteries, which are necessary for the mobile device industry such as electric vehicles and mobile phones, has exploded, and the demand for copper foil, which is necessary for lithium secondary batteries with high energy density and stability, has also increased rapidly. As a result, copper foil, which is a very thin copper film used as a negative electrode current collector for secondary batteries, has attracted attention as one of the major materials in the electronic device industry. Such copper foil is usually divided into electrolytic copper foil and rolled copper foil depending on the manufacturing method, and since each has its own advantages and disadvantages, the preferred method varies depending on the application.
[0003] In particular, the manufacturing process of electrolytic copper foil is mainly done by continuous production using the roll-to-roll method, which allows for mass production and has the advantage of being able to produce wide and thin copper foil, so electrolytic copper foil is mainly used for lithium secondary batteries. Recently, copper foil with a thickness of 10 μm or less is required, and copper foils with a thickness of 8 μm and 6 μm are mainly used.
[0004] In general, the physical properties of electrolytic copper foils, such as tensile strength, elongation rate, roughness, etc., are important and are controlled accordingly. In addition, the thinner the thickness of the electrolytic copper foil, the more the surface of the copper foil affects the physical properties of the copper foil, such as tensile strength, elongation rate, roughness, etc., and therefore the relationship between each physical property is considered important.
[0005] A number of methods and technologies for controlling physical properties have been reported to achieve the basic physical properties of copper foil. In particular, as a method for controlling such physical properties, a method is used in which one or more types of organic compound-based additives are added to change the total amount of additives added in a complex manner. For example, as a method for manufacturing electrolytic copper foil by controlling physical properties, Patent Document 1 discloses a technology for improving the strength of electrolytic copper foil by improving manufacturing stability using an additive that is a thiourea-based compound, and for improving the surface gloss of electrolytic copper foil by using a sulfonic acid or a metal salt thereof that is a compound containing sulfur atoms. In addition, Patent Document 2 discloses a technology for manufacturing electrolytic copper foil in which the relative thickness of discontinuous layers to continuous layers is minimized by appropriately controlling the composition of an electrolyte, the current density, or the type and content of additives added to the electrolyte.
[0006] However, when such additives are used, there is a problem that only one physical property of the copper foil cannot be selectively controlled. For example, when an additive that adjusts the elongation rate among physical properties is used, not only can the elongation rate be maintained or improved, but also affects the change in other physical properties such as roughness or glossiness, so that the amount of other additives related to roughness or glossiness must also be changed.
[0007] In order to solve these problems, there is a need for a method for controlling the physical properties of an electrolytic copper foil, which can easily adjust the physical properties such as elongation, tensile strength, and roughness within the general range of the physical properties of the electrolytic copper foil, and a method for manufacturing the same. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Korean Patent No. 1571064 [Patent Document 2] Korean Patent No. 1126831 Summary of the Invention [Problem to be solved by the invention]
[0009] The present invention has been invented to solve the above problems, and an object of the present invention is to easily adjust physical properties such as elongation, tensile strength, and roughness within the general physical property range of an electrodeposited copper foil. Another object of the present invention is to solve the problem of having to change the amounts of other additives in a complex manner, simplify the process for controlling the physical properties of an electrodeposited copper foil, and reduce the associated process costs and additive costs. [Means for solving the problem]
[0010] The method for controlling the physical properties of an electrolytic copper foil of the present invention controls the physical properties including tensile strength, elongation rate and roughness by adjusting the gloss of the electrolytic copper foil by adding a gloss adjuster, and the gloss range is 35 to 400 GU (60°).
[0011] The gloss level is adjusted to adjust the stretch ratio according to the following formula 1.
[0012] Formula 1: E=-3.15×10 -5 ×G 2 +0.006×G+7.19 (G: gloss (GU (60°)), E: elongation rate (%))
[0013] The gloss level is adjusted to adjust the tensile strength according to the following formula 2.
[0014] Formula 2: T=1.25×10 -4 ×G 2 -0.104×G+49.8 (G: gloss (GU(60°)), T: tensile strength (kgf / mm 2 ))
[0015] The gloss level is adjusted to adjust the roughness according to the following formula 3.
[0016] Equation 3: R=7.59×10 -6 ×G 2 -0.005×G+1.80 (G: gloss (GU(60°)), R: roughness (μm))
[0017] The gloss regulator includes at least one of sulfonic acid, which is a compound containing a sulfur atom, or a metal salt thereof, such as thiophosphoric acid-tris-(ω-sulfopropyl) ester trisodium salt, 3-mercapto-1-propanesulfonic acid (MPS), bis-(3-sulfopropyl)-disulfide disodium salt (SPS), and thioglycolic acid.
[0018] The concentration of the gloss regulator is 12 ppm to 40 ppm, and preferably 18 ppm to 28 ppm.
[0019] The method for producing an electrolytic copper foil of the present invention includes the steps of: preparing an electrolyte by dissolving copper ions in sulfate ions; and adding, to the electrolyte, a stretch rate regulator for maintaining and improving the stretch rate, or a tensile strength regulator for maintaining and improving the tensile strength, or both; controlling the physical properties of the electrolytic copper foil by the method for controlling physical properties of the electrolytic copper foil by adding a gloss regulator for improving gloss; and forming an electrolytic copper foil by supplying an electric current while supplying the electrolyte containing the additives to a foil-making machine in which a rotating cathode drum and an anode are spaced apart from each other.
[0020] The concentration of the copper ions in the electrolytic solution is 70 g / L to 100 g / L, and the concentration of the sulfate ions is 80 g / L to 150 g / L.
[0021] The stretch rate regulator includes at least one of carboxymethyl cellulose, polyethylene glycol, hydroxyethyl cellulose (HEC), octanediol-bis-polyalkylene glycol ether, and polyglycerin, which are nonionic water-soluble polymers.
[0022] The tensile strength modifier includes at least one of a thiourea-based compound or a compound in which a thiol group is linked to a nitrogen-containing heterocycle, such as diethylthiourea, ethylenethiourea, acetylenethiourea, 2-thiouracil, 2-mercapto-5-benzoimidazole sulfonic acid sodium salt, sodium 3-(5-mercapto-1-tetrazolyl)benzene sulfonate, and 2-mercapto benzothiazole.
[0023] The gloss regulator includes at least one of sulfonic acid, which is a compound containing a sulfur atom, or a metal salt thereof, such as thiophosphoric acid-tris-(ω-sulfopropyl) ester trisodium salt, 3-mercapto-1-propanesulfonic acid (MPS), bis-(3-sulfopropyl)-disulfide disodium salt (SPS), and thioglycolic acid.
[0024] The concentration of the gloss regulator is 12 to 40 ppm, preferably 18 to 28 ppm. Effect of the Invention
[0025] According to the present invention, it is possible to easily adjust the physical properties such as tensile strength, elongation rate, and roughness of the electrolytic copper foil by adjusting only the gloss of the electrolytic copper foil.
[0026] In addition, according to the present invention, by adjusting only one physical property of the electrolytic copper foil, namely glossiness, other physical properties of the copper foil can be adjusted to desired values, so that it is not necessary to adjust the amounts of various additives added in a complex manner to adjust the physical properties of the electrolytic copper foil. Therefore, the process for controlling the physical properties of the electrolytic copper foil is simplified, and the associated process costs and additive costs can be reduced. [Brief description of the drawings]
[0027] [Figure 1] 1 is a graph showing the relationship between gloss and stretch ratio according to the present invention. [Diagram 2] 1 is a graph showing the relationship of tensile strength to gloss according to the present invention. [Diagram 3] 4 is a graph showing the relationship of roughness to gloss according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] Hereinafter, the method for controlling the physical properties of electrolytic copper foil and the method for manufacturing copper foil according to the present invention will be described in more detail with reference to the drawings.
[0029] The electrolytic copper foil according to the present invention can be produced using the following electrolyte.
[0030] (Electrolyte production) In order to manufacture electrolytic copper foil, an electrolyte is prepared by adjusting the copper ions and sulfate ions, and additives for adjusting the basic physical properties of the copper foil are added to the electrolyte.
[0031] The electrolyte has a copper ion concentration of 70 to 100 g / L and a sulfate ion concentration of 80 to 150 g / L, and the concentrations of copper and sulfate ions vary depending on the manufacturing conditions of the electrolytic copper foil.
[0032] Here, the raw material of the copper ions is a raw material containing copper such as Cu Powder, Cu Scrap (waste electric wire, chopping Cu, etc.), copper sulfate, copper oxide, copper carbonate, etc., and any copper raw material that can be dissolved in sulfuric acid can be used.
[0033] The electrolyte contains additives necessary to adjust the physical properties of the copper foil, and the additives usually include additives that adjust one or more of the physical properties of elongation, tensile strength, and gloss.
[0034] A draw rate regulator for controlling the draw rate of the copper foil and a tensile strength regulator for controlling the tensile strength of the copper foil are added to the electrolyte.
[0035] Here, the stretch rate regulator for maintaining and improving the stretch rate includes at least one of nonionic water-soluble polymers such as carboxymethyl cellulose, polyethylene glycol, hydroxyethyl cellulose (HEC), octanediol-bis-polyalkylene glycol ether, and polyglycerin.
[0036] The tensile strength modifier for maintaining and improving the tensile strength includes at least one of a thiourea compound or a compound in which a thiol group is linked to a nitrogen-containing heterocycle, such as diethylthiourea, ethylenethiourea, acetylenethiourea, 2-thiouracil, 2-mercapto-5-benzoimidazole sulfonic acid sodium salt, sodium 3-(5-mercapto-1-tetrazolyl)benzene sulfonate, and 2-mercapto benzothiazole.
[0037] Then, a gloss regulator for adjusting the gloss of the copper foil is added to the electrolyte to manufacture an electrolytic copper foil, and the gloss regulator for improving the gloss includes at least one of sulfonic acid, which is a compound containing a sulfur atom, or a metal salt thereof, such as thiophosphoric acid-tris-(ω-sulfopropyl)ester trisodium salt, 3-mercapto-1-propanesulfonic acid (MPS), bis-(3-sulfopropyl)-disulfide disodium salt (SPS), and thioglycolic acid.
[0038] The gloss regulator is added so that its concentration in the electrolyte is adjusted to 12 to 40 ppm, or preferably 18 to 28 ppm. If the concentration of the gloss regulator is higher than 40 ppm, the tensile strength and elongation of the copper foil are reduced, making the copper foil more likely to break. If the concentration of the gloss regulator is lower than 12 ppm, the curling property of the electrolytic copper foil becomes severe, making the copper foil difficult to handle.
[0039] (Method of manufacturing electrolytic copper foil) In the manufacturing method of electrolytic copper foil, the electrolyte prepared as described above is supplied under the following conditions to a foil-making machine in which a rotating cathode drum with a Ti surface and an anode using a DSE (Dimentional Stable Electrode) plate containing platinum group elements in Ti are kept at a constant distance from each other.
[0040] Electrolyte temperature: 45~55℃ Electrolyte flow rate: 1,800~3,500L / hr Current density: 4,500~6,500A / m 2
[0041] (Method of controlling the physical properties of electrolytic copper foil) According to one embodiment of the present invention, a gloss regulator is added to adjust the gloss within a range of 35 to 400 GU (60°), or preferably 120 to 250 GU (60°), to control physical properties including tensile strength, elongation rate, and roughness.
[0042] In this case, the physical properties of the electrolytic copper foil are controlled by the following formulas 1 to 3, and the desired tensile strength, elongation rate, and roughness values can be obtained by controlling only the glossiness, so that the physical properties of the electrolytic copper foil can be easily controlled.
[0043] Formula 1: E=-3.15×10 -5 ×G 2 +0.006×G+7.19 Formula 2: T=1.25×10 -4 ×G 2 -0.104×G+49.8 Equation 3: R=7.59×10 -6 ×G2 -0.005×G+1.80 (Here, "G" is the gloss (GU(60°)) of the electrodeposited copper foil, and "E", "T", and "R" are the elongation rate (%) and tensile strength (kgf / mm 2 ) and roughness (μm).
[0044] The gloss of the electrolytic copper foil is controlled to 120-250GU (60°). The elongation of the electrolytic copper foil is 6.5-9%, and the tensile strength is 30-40kgf / mm 2 and the roughness is 0.8 to 1.5 μm.
[0045] According to an embodiment of the present invention, an electrolytic copper foil for a negative electrode current collector of a secondary battery can be manufactured.
[0046] Hereinafter, a process of deriving a correlation equation between the gloss and other physical properties of the electrodeposited copper foil based on the results of each experiment under different experimental conditions will be described in detail.
[0047] <Experimental Example 1> The electrolyte was formulated to contain 80g / L copper, 100g / L sulfuric acid, 10ppm of elongation modifier (HEC), and 25ppm of tensile strength modifier (DTE). The electrolyte was supplied to an electrolytic cell equipped with a rotating cathode drum (530φ×280w) at a flow rate of 3,000L / hr while maintaining its temperature at 54°C. In addition, bis-(3-sulfopropyl)-disulfide disodium salt (SPS), a gloss modifier, was added to the electrolyte while adjusting the concentration to 12-40ppm.
[0048] In the copper foil electrolysis process, the current is 5,769A / m 2 A constant current method was used to supply a current density of 1.0 μm, and the rotating cathode drum was rotated at a speed of 1.47 m / min to continuously produce an electrolytic copper foil having a thickness of 8 μm.
[0049] <Experimental Example 2> In Experimental Example 2, the experiment was carried out under the same conditions as in Experimental Example 1, except that the concentration of the elongation modifier was changed to within the range of 5 to 15 ppm and the concentration of the tensile strength modifier was changed to within the range of 20 to 30 ppm.
[0050] <Experimental Example 3> In Experimental Example 3, an experiment was conducted under the same conditions as in Experimental Example 1, except that the copper ion concentration in the electrolyte was changed to within the range of 70 g / L to 100 g / L and the sulfate ion concentration was changed to within the range of 80 g / L to 150 g / L.
[0051] <Experimental Example 4> In Experimental Example 4, the current density in Experimental Example 1 was changed to 4,500 to 6,500 A / m 2 The experiment was conducted under the same conditions, except that the rotation speed of the rotating cathode drum was changed to within the range of 1.3 to 1.6 (m / min).
[0052] (Measurement of elongation rate, tensile strength and roughness by gloss change) The electrolytic copper foils obtained in Experimental Examples 1 to 4 were heat-treated at a temperature of 70° C. for 18 hours, and then the gloss, elongation rate, tensile strength and roughness of the electrolytic copper foils were measured.
[0053] Figure 1 shows the measured values of the elongation rate as a function of the gloss of the electrolytic copper foil, Figure 2 shows the measured values of the tensile strength as a function of the gloss of the electrolytic copper foil, and Figure 3 shows the measured values of the roughness as a function of the gloss of the electrolytic copper foil.
[0054] Fig. 1 is a graph showing the relationship between gloss (x-axis) and elongation (y-axis) by measuring the elongation of the electrodeposited copper foils obtained in the above Experimental Examples 1 to 4. From the graph plotting the physical property data of gloss and elongation, the correlation between gloss and elongation when the gloss is in the range of 35 to 400GU (60°) can be derived. Specifically, the correlation between each gloss and elongation is derived by extrapolation (a method of estimating values outside the range when the function value is known only within a certain range of variables), and the correlation between gloss and elongation is as shown in the following formula 1.
[0055] Formula 1: E=-3.15×10-5 ×G 2 +0.006×G+7.19 (Here, "G" indicates the gloss (GU (60 °)) of the electrolytic copper foil, and "E" indicates the elongation rate (%) of the electrolytic copper foil.)
[0056] Fig. 2 is a graph showing the relationship between gloss (x-axis) and tensile strength (y-axis) by measuring the tensile strength of the electrodeposited copper foils obtained in the above Experimental Examples 1 to 4. From the graph plotting the physical property data of gloss and tensile strength, the correlation between gloss and tensile strength when the gloss is in the range of 35 to 400 GU (60°) can be derived. Specifically, the correlation between each gloss and tensile strength is derived by extrapolation, and the correlation between gloss and tensile strength is as shown in the following formula 2.
[0057] Formula 2: T=1.25×10 -4 ×G 2 -0.104×G+49.8 (Here, "G" is the gloss of the electrolytic copper foil (GU(60°)), and "T" is the tensile strength of the electrolytic copper foil (kgf / mm 2 ) is shown.
[0058] 3 is a graph showing the relationship between the glossiness (x-axis) and the roughness (y-axis) by measuring the roughness of the electrodeposited copper foils obtained in the above Experimental Examples 1 to 4. The graph plotting the physical property data of glossiness and roughness allows the correlation between glossiness and roughness when the glossiness is within the range of 35 to 400 GU (60°) to be derived. Specifically, the correlation between each glossiness and roughness is derived by extrapolation, and the correlation between glossiness and roughness is as shown in the following formula 3.
[0059] Equation 3: R=7.59×10 -6 ×G 2 -0.005×G+1.80 (Here, "G" indicates the gloss (GU (60 °)) of the electrolytic copper foil, and "R" indicates the roughness (μm) of the electrolytic copper foil.)
[0060] In order to evaluate whether the physical properties of the electrolytic copper foil can be controlled by the above formulas 1 to 3, the following experiment was carried out.
[0061] (Manufacturing of electrolytic copper foil) [Examples 1 to 9] The electrolyte was formulated to contain 80g / L copper, 100g / L sulfuric acid, 10ppm HEC, and 25ppm DTE. A gloss modifier (SPS) was also added to the electrolyte at a concentration of 12-40ppm.
[0062] The electrolytic solution was supplied to an electrolytic cell equipped with a rotating cathode drum (530φ×280w) at a flow rate of 3,000 L / hr while maintaining the temperature at 54° C.
[0063] In the copper foil electrolysis process, the current is 5,769A / m 2 A current density of 1.0 μm was supplied by the constant current method, and the rotating cathode drum was rotated at a speed of 1.47 m / min to continuously produce an electrolytic copper foil having a thickness of 8 μm.
[0064] [Examples 10 to 13] An electrolytic copper foil having a thickness of 8 μm was manufactured under the same conditions as in Example 1, except that the concentrations of the elongation modifier (HEC) and the tensile strength modifier (DTE) in the electrolyte were changed as shown in Table 1.
[0065] [Examples 14 to 17] An electrolytic copper foil having a thickness of 8 μm was produced under the same conditions as in Example 1, except that the copper and sulfuric acid concentrations in the electrolyte were changed as shown in Table 1.
[0066] [Examples 18 to 21] An electrolytic copper foil having a thickness of 8 μm was produced under the same conditions as in Example 1, except that the current density and the rotation speed of the rotating cathode drum during the electrolysis of the copper foil were changed as shown in Table 1.
[0067] [Table 1]
[0068] (Measurement of physical properties of electrolytic copper foil) The electrolytic copper foils prepared in Examples 1 to 21 were heat-treated at a temperature of 70° C. for 18 hours, and the physical properties including gloss, elongation, tensile strength and roughness of the electrolytic copper foils were measured and shown in Table 2.
[0069] (Gloss measurement) The gloss level was measured by cutting the electrolytic copper foil into a 10 cm x 10 cm piece, irradiating the surface of the copper foil with a measuring light at an incident angle of 60° along the machine direction (MD) of the copper foil, and measuring the intensity of the light reflected at a reflection angle of 60° in accordance with JIS B 0601, which is a method for measuring gloss level.
[0070] (Measurement of tensile strength / elongation rate) The tensile strength and elongation were measured in accordance with JIS C 6511 using an electrolytic copper foil tensile tester (MINOS-005:MTDI). The measurement conditions were room temperature (25°C ± 10°C), chuck distance 50 mm, and displacement speed 50 mm / min.
[0071] (Roughness measurement) The measurements were made in accordance with JIS B 0601 (JIS 1994), which is a method for measuring roughness, using a roughness meter (SJ-411: MITUTOYO) in the flow direction (MD) and the perpendicular direction of the copper foil.
[0072] Through the above measurements, the elongation rate, tensile strength, and roughness depending on the change in gloss were measured, and the elongation rate, tensile strength, and roughness depending on the change in gloss were calculated using Equations 1 to 3. In addition, the error between the measured value and the calculated value was calculated, and the results are shown in Table 2 below. Here, the error between the calculated value and the measured value for each physical property was calculated as ((calculated value / measured value)×100-100)(%).
[0073] [Table 2]
[0074] According to Table 2, if the gloss is adjusted to within a range of 35 to 400GU (60°), preferably 120 to 250GU (60°) by adding an additive bis-(3-sulfopropyl)-disulfide disodium salt (SPS) during the preparation of the electrolyte, the elongation rate, tensile strength, and roughness, which are the physical properties of the electrodeposited copper foil, can be calculated using Equations 1 to 3. In particular, Equations 1 to 3 can be used even if the concentration of the tensile strength regulator or elongation regulator, the copper and sulfate ion concentrations of the electrolyte, or the current density and the rotation speed of the rotating cathode drum in the electrolysis process are changed, and the results are within an error range of ±5% from the actually measured values, so that they can be used in actual operations.
[0075] Therefore, according to the present invention, by adjusting only one physical property of the electrodeposited copper foil, namely the glossiness, other physical properties can be adjusted to desired values, so there is no need to adjust the amounts of various additives added in combination to adjust the physical properties of the electrodeposited copper foil. Since other physical properties of the electrodeposited copper foil can be appropriately controlled by adjusting only the glossiness, the process for controlling the physical properties of the electrodeposited copper foil is simplified, and the associated process costs and additive costs can be reduced.
[0076] Those skilled in the art should understand that the present invention can be implemented in other specific forms without changing its technical idea or essential features. Therefore, the above-described embodiments are illustrative in all respects and should not be interpreted as limiting. The scope of the present invention is defined by the claims set forth below, and all modifications and variations derived from the meaning and scope of the claims and their equivalent concepts should be interpreted as being included in the scope of the present invention.
Claims
1. A gloss regulator is added to adjust the gloss of the electrodeposited copper foil, thereby controlling physical properties including tensile strength, elongation rate and roughness; The gloss range is 35 to 400 GU (60°), The tensile strength, the elongation rate and the roughness are adjusted by adjusting the glossiness according to a predetermined correlation with the glossiness, The method for controlling the physical properties of an electrolytic copper foil includes adjusting the gloss and controlling the elongation ratio according to the following formula 1: Formula 1: E = -3.15 x 10 -5 x G 2 + 0.006 x G + 7.19 (G: gloss (GU(60°)), E: stretch rate (%))
2. The method for controlling physical properties of an electrolytic copper foil according to claim 1, wherein the gloss is adjusted to adjust the tensile strength according to the following formula 2: Formula 2: T=1.25×10 -4 xG 2 -0.104 x G + 49.8 (G: gloss (GU(60°)), T: tensile strength (kgf / mm 2 ))
3. The method for controlling physical properties of an electrolytic copper foil according to claim 1, wherein the gloss is adjusted to adjust the roughness according to the following formula 3: Formula 3: R=7.59×10 -6 xG 2 -0.005 x G + 1.80 (G: gloss (GU (60°)), R: roughness (μm))
4. The method for controlling physical properties of an electrolytic copper foil according to claim 2, wherein the gloss is adjusted to adjust the roughness according to the following formula 3: Formula 3: R=7.59×10 -6 xG 2 -0.005 x G + 1.80 (G: gloss (GU (60°)), R: roughness (μm))
5. The gloss regulator is a compound containing a sulfonic acid or a metal salt thereof, and includes at least one of thiophosphoric acid-tris-(ω-sulfopropyl)ester trisodium salt, 3-mercapto-1-propanesulfonic acid (MPS), bis-(3-sulfopropyl)-disulfide disodium salt (SPS), and thioglycolic acid.
6. The method for controlling physical properties of an electrolytic copper foil according to claim 1, wherein the concentration of the gloss regulator is 12 to 40 ppm.
7. The method for controlling physical properties of an electrolytic copper foil according to claim 6, wherein the concentration of the gloss regulator is 18 to 28 ppm.
8. preparing an electrolyte by dissolving copper ions in sulfate ions, and adding to the electrolyte a stretch rate regulator for maintaining and improving the stretch rate, or a tensile strength regulator for maintaining and improving the tensile strength, or both; A step of controlling the physical properties of the electrolytic copper foil by the method of controlling the physical properties of the electrolytic copper foil according to claim 1 by adding a gloss regulator for improving the gloss; and supplying an electric current while supplying the electrolyte containing the additive to a foil-making machine in which a rotating cathode drum and an anode are spaced apart from each other to form an electrolytic copper foil.
9. 9. The method for producing an electrolytic copper foil according to claim 8, wherein the concentration of the copper ions in the electrolytic solution is 70 g / L to 100 g / L, and the concentration of the sulfate ions in the electrolytic solution is 80 g / L to 150 g / L.
10. The method for producing an electrolytic copper foil according to claim 8 or 9, wherein the elongation rate regulator is a nonionic water-soluble polymer, and includes at least one of carboxymethyl cellulose, polyethylene glycol, hydroxyethyl cellulose (HEC), octanediol-bis-polyalkylene glycol ether, and polyglycerin.
11. The tensile strength modifier is a thiourea compound or a compound in which a thiol group is linked to a nitrogen-containing heterocycle, such as diethylthiourea, ethylenethiourea, acetylenethiourea, 2-thiouracil, 2-mercapto-5-benzimidazole sulfonic acid sodium salt, sodium 3-(5-mercapto-1-tetrazolyl)benzene sulfonate, and 2-mercaptobenzothiazole. The method for producing an electrolytic copper foil according to claim 8 or 9, further comprising at least one of the following:
12. The method for producing an electrolytic copper foil according to claim 8 or 9, wherein the gloss regulator includes at least one of sulfonic acid, which is a compound containing a sulfur atom, or a metal salt thereof, which is thiophosphoric acid-tris-(ω-sulfopropyl)ester trisodium salt, 3-mercapto-1-propanesulfonic acid (MPS), bis-(3-sulfopropyl)-disulfide disodium salt (SPS), and thioglycolic acid.
13. The method for producing an electrolytic copper foil according to claim 8 or 9, wherein the concentration of the gloss regulator is 12 to 40 ppm.
14. The method for producing an electrolytic copper foil according to claim 13, wherein the concentration of the gloss regulator is 18 to 28 ppm.
Citation Information
Patent Citations
Status career storage system
JP1983010249A
Electrolytic copper foil, surface treated copper foil using the electrolytic copper foil, copper-clad laminated plate using the surface treated copper foil, and method for manufacturing the electrolytic copper foil
JP2008101267A
Electrolytic copper foil and method for producing the same
JP2014132106A
Electrolytic copper foil and method for producing the electrolytic copper foil
JP2014224321A
Electrolytic copper foil, lithium ion secondary battery negative electrode and lithium ion secondary battery, printed wiring board, and electromagnetic wave-shielding material
JP2017014608A